Can native plantings encourage native and beneficial invertebrates on Canterbury dairy farms?. Issue 2 (3rd July 2019) - Curtis, K.; Bowie, M. H.; Hodge, S.
ABSTRACT: Farming intensification negatively effects native habitat and associated biodiversity in New Zealand. Planting native species around field margins has been proposed as a means of restoring biodiversity within this highly modified landscape. To test this hypothesis, we collected invertebrates on a dairy farm at Lincoln, Canterbury, in three habitat types: native plantings in field corners, native plantings along a double fence line, and pasture. Invertebrates were collected from pitfall traps, yellow pan traps, wooden discs and leaf litter samples were collected from the sites over summer. Assemblages of spiders, flying insects, slugs and litter mites in the planted areas had distinct compositions compared with those found in adjacent pasture. Species richness of native spiders was increased in the planted areas compared with adjacent pasture, as was the abundance of ecosystem service providers, such as honeybees, parasitoid wasps and hoverflies. Exotic slugs were significantly more abundant under discs in pasture than in planted areas. However, not all native or beneficial invertebrates responded positively to the planted areas. Further research is required to examine whether these results are repeatable at other locations, if invertebrate assemblages at this location develop further over time, and to evaluate whether any perceived benefits of these service providers can be quantified in terms of meaningful endpoints such as reduced pest levels and/or increases in yield.